Understanding the Characteristics of Pig Butchering Scams: Impact on Victims and Challenges for Law Enforcement in Indonesia - Aissyach, Aissyach Noor Chairinovadanti; Sigid, Sigid Suseno; Budi, Budi Arta Atmaja (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The pig butchering scam mode or